Factors Important in the Selection of a Rhinology/Skull Base Surgery Fellow: A National Survey of Fellowship Directors. Issue 2 (March 2021) - Johnson, Jared; Stathakios, James; Chung, Michael T.; Engel, Ricardo; Folbe, Adam
Background: The numbers of Rhinology/Skull Base Surgery fellowship programs and applicants have been increasing in recent years. However, little information is currently available with regards to the most important aspects of the application process. Objective: The goal of this study was to determine the factors that Rhinology/Skull Base Surgery fellowship directors consider most important when selecting a fellow. Methods: An anonymous, online survey was distributed to current Rhinology/Skull Base Surgery fellowship directors. 28 of 31 fellowship directors (90%) completed the survey. Respondents were asked to provide basic information regarding the program and to rank various selection factors they deem most important. Results: For assessing the quality of an application, fellowship directors placed the highest value on LORs. Research experience and publications were also important considerations. The traditional strength of an applicant's residency program was a factor, while medical school performance, USMLE scores, and OTE score did not play a significant role in the selection process. For subjective assessment of applicants, the most value was placed on faculty assessment of the applicant during their interview. Attention was also given to personality fit with the program and the perceived maturity and initiative of the applicant. Conclusion: Numerous academic achievements and personal characteristics are given consideration in the Rhinology/Skull Base Surgery fellowship selection process, but recommendation from a trusted colleague and performance on interviews were viewed to be the most critical factors for fellowship programs in selecting applicants. This is consistent with studies that have explored the selection process for other otolaryngology fellowship programs.